Flow Characteristics of a Porous Pipe Irrigation Lateral - Mohd Soom, Mohd Amin; Lim, C. W.; Zakaria, Abdul Aziz (Universiti Putra Malaysia Press, 1998)
Porous pipe is useful for both surface and subsurface microirrigation systems. However very little information is available about its discharge uniformity and operating characteristics. This paper presents work done at CPM on the hydraulics of porous pipe to determine such performance criteria as the pressure-discharge relationship and friction head loss. Several lengths of imported porous pipe were subjected to various upstream pressure inputs La determine the average discharge along the lateral and the associated pressure losses. The flow in the emitter lateral was found to be highly sensitive to pressure with discharge exponent ranging from 1.07 to 1.67. Graphs were developed to facilitate design of porous pipe laterals for "arious applications.